A Short Note on Sedimentary Rocks of the Barru Area, South Sulawesi - Asri Jaya; Sufriadin Sufriadin; Irzal Nur (Berita Sedimentologi, 2011)
Barru area comprises four sedimentary sequences that include Cretaceous flysch sediment of Balangbaru Formation in the lower part, overlain by Tertiary terrestrial sediments of Mallawa, shallow-marine redeposited carbonate of Tonasa and volcaniclastics sediment of Camba Formations in the upper part. Three of these sequences show characteristics of deep-marine depositional system that are associated with turbidite – debris flow facies and post-depositional deformation structures. Their occurrences are interpreted to have been controlled by regional tectonics, in particular during the redeposition of the Tonasa Formation carbonates and also the volcaniclastic-epiclastic of the Camba Formation. The difficulties in defining sedimentary basin in this area might possibly be, in part, due to the basin was modified during or after the depositional period. Therefore, it is very hard to trace the basin continuously in only one site.